Seasonal variations in urinary calcium, volume, and vitamin D in kidney stone formers - Attalla, Kyrollis (Int Braz J Urol, 2018)
OBJECTIVES: To investigate the seasonal variations in urinary calcium, serum vitamin D, and urinary volume in patients with a history of nephrolithiasis. MATERIALS AND METHODS: Patients included were those who completed a 24-hour urine metabolic evaluation on two occasions; one in summer (June-Aug) and one in winter (Nov-Jan), and who had not started any medications or been instructed on dietary modifications in the interval between the two tests that may have impacted the results. Patients were excluded if they were on thiazide diuretics or were taking calcium and / or Vitamin D supplementation. Welch's t-test was used to compare the difference in average summer and winter values. Unpaired Student t-test was used to compare baseline parameters (age, BMI), and Paired Student t-test was used to compare average seasonal measurements in men vs. women. RESULTS: 136 patients were identified who were not taking calcium or vitamin D supplements or thiazide diuretics, and who were not instructed on dietary modifications in the interval between the two measured parameters. No significant differences were observed when comparing male to female baseline parameters of age or BMI (Table-1). Average 24-hour urine calcium was higher (226.60) in the winter than in summer (194.18) and was significant in males (p = 0.014) and females (p < 0.001). No significant seasonal difference was seen in 24-hour urine volume or serum vitamin D levels. CONCLUSIONS: Urinary calcium is higher in winter months compared to summer months. As such, tailoring medical preventative strategies to the time of year may be helpful.